Staphylococcus aureus ftnA 3’-Untranslated Region Modulates Ferritin Production Facilitating Growth Under Iron Starvation Conditions - Menendez-Gil, Pilar; Catalan-Moreno, Arancha; Caballero, Carlos J.; Toledo-Arana, Alejandro (Frontiers in Microbiology, 2022)
Iron acquisition and modulation of its intracellular concentration is critical for the development of all living organisms. So far, several proteins have been described to be involved in iron homeostasis. Among them, ferritins act as the major iron storage proteins, sequestering internalized iron and modulating its concentration inside bacterial cells. We previously described that the deletion of the 3’ untranslated region (3’UTR) of the ftnA gene, which codes for ferritin in Staphylococcus aureus, increased the ftnA mRNA and ferritin levels. Here, we show that the ferritin levels are affected by RNase III and PNPase, which target the ftnA 3’UTR. Rifampicin mRNA stability experiments revealed that the half-life of the ftnA mRNA is affected by both RNase III, and the ftnA 3’UTR. A transcriptional fusion of the ftnA 3’UTR to the gfp reporter gene decreased GFP expression, indicating that the ftnA 3’UTR could work as an independent module. Additionally, a chromosomal deletion of the ftnA 3’UTR impaired S. aureus growth under conditions of iron starvation. Overall, this work highlights the biological relevance of the ftnA 3’UTR for iron homeostasis in S. aureus.